Antioxidant Activity of Aqueous Extract of Ginger (Zingiber Officinale W. Roscoe) and Margosa (Azadirachta Indica A. Juss) in the Districts of Nampula and Angoche (REMUNOM, 2025)
Antioxidants are substances that, when present in the body, compromise the harmful action of free radicals. These radicals are considered major cause of various chronic no communicable diseases like inflammation, malignant tumors, cardiovascular diseases, cancer as well as accelerate the aging process. Epidemiological studies state that proper intake of plant products reduces the risk of a variety of chronic diseases caused by these substances. Effect, attributed to compounds that have antioxidant activity in plants: vitamins A, C and E, phenolic compounds, especially flavonoids and carotenoids. The rhizome of the Ginger and the plant of Margosa are vegetables that had the capacity to fight the radicals. From this, we aimed to analyze the antioxidant activity of aqueous extract of Ginger and Margosa in the prevention of diseases caused by free radicals. As regards the analysis of the antioxidant property, the hydroalcoholic extract of the leaves of A. indica and of zingiber officinale W. Roscoe method of the phosphomolybdenum ammonium were obtained. The results obtained for ABTS activity (200.37 ± 0.59a and 152.86 ± 0.95b mg VCEAC 100g-1), phenolic compounds (201.48 ± 1.46a and 196.34 ± 0.59b GAE), vitamin A (2322.00 ± 12.00a and 0.00 ± 0.00 b (61.74 ± 1.38a and 82.01 ± 1.74b%) and minerals detected and studied are: calcium presented the highest content in Margosa (180.87 ± 5.40 e 3.60 ± 0.56b mg / 100g) (874.00 mg/L), followed by potassium (271.50 mg/L), magnesium (172.78 mg/L) and sodium (22.81), Ginger showed higher value (412.50 mg/L), zinc and iron (48.00 and 19.01 mg/L). these results show clearly that the extract of Margosa presented good antioxidant capacity when compared with the extracts of Ginger, as it can be verified there were statistically significant differences between the two treatments. These components present in these vegetables are those that showed an interest for the discussion of the results in relation to the prevention of chronic no communicable diseases.